Design, modeling and control of llc resonant converter for attenuation of second harmonic current ripples in electric vehicle on-board charger - Nourhan Ahmed Abdulhamid Hassen; Ahmed Lotfy El-Refai (2024)
The main objective of this thesis is to apply a proportional integral resonant (PIR) controller to attenuate the second harmonic (100 Hz) current ripple in an electric vehicle onboard charger that originates from the rectified 50 Hz AC power grid mains. First, we design and analyze the LLC resonant converter with full bridge inverter and full wave center-tapped rectifier. After that, we obtain the small signal model of the LLC resonant converter by using a time domain simulation method. We then discuss the design methodology of a conventional proportional integral (PI) controller in addition to a resonant (R) controller which is used in parallel with the PI-controller to form the PIR-controller. By using the designed PIR-controller, we can achieve higher power density, higher reliability, and lower cost for the designed onboard charger in addition to increasing the Li-ion battery lifespan when compared to conventional attenuation methods for low-frequency current ripple
(3GdgOa GdQFjSi ef gPg GdQSGdI gh JWHjb GdeJMce GdJfGSHj GdJcGedj GdQfGf(B(PIR controller) (3dJNaja JehLGJ GdJjGQ PGJ GdJhGab GdKGfi (B(100 (3gQJR(B) (3ai GdTGMf GdehLhO Ydi eJf GdSjGQI GdcgQHGFjI GdJi JfTC ef JhMjO GdbOQI GdJQOOjI PGJ GdJPHPH (B50 (3gQJR dTHcI GdcgQHGA GdQFjSjI(B. (3GhdG, fbhe HJUeje hJMdjd GdeMhd GdQfGf(BLLC (3hGdPi jJchf ef GdeMhd GdYGcS Ph GdbfWQI GdcGedI ehMO GdehLI Ph GdbfWQI GdcGedI PGJ fbWI JaQY eQcRjI(B. (3HYO Pdc, fMUd Ydi fehPL GdETGQI GdUZjQI ddeMhd GdQfGf(BLLC (3HGSJNOGe WQjbI eMGcGI aj GdeLGd GdRefj(B. (3ffGbT HYO Pdc efgLjI JUeje JbdjOjI dhMOI GdeJMce GdJfGSHj GdJcGedj(B(PI controller) (3HGdEVGaI Edi hMOI GdeJMce GdQfGf (B(R controller) (3GdJj jJe GSJNOGegG HGdJhGRj eY hMOI GdeJMce(B(PI-controller) (3dJTcjd hMOI JMce(B(PIR-controller) . (3HGSJNOGe hMOI GdeJMce GdJj Je JUejegG(B(PIR-controller) (3, jecffG JMbjb cKGaI WGbI CYdi hGYJeGOjI GaVd hJcdaI Cbd ddTGMf GdeOeL GdPj Je JUejeg HGdEVGaI Edi RjGOI YeQ HWGQjI GddjKjhe Gjhf HGdebGQfI eY WQb GdJNaja GdJbdjOjI dJehLGJ GdJjGQ efNaVI GdJQOO(B.s
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 85-90.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Electric vehicles; electric vehicle -- proportional integral resonant (PIR) controller -- LLC resonant converter -- onboard charger -- low frequency current ripple